Predictors for profound blood pressure response in patients undergoing renal sympathetic denervation. Issue 7 (July 2018) - Fengler, Karl; Rommel, Karl-Philipp; Blazek, Stephan; von Roeder, Maximilian; Besler, Christian; Hartung, Philipp; Desch, Steffen; Thiele, Holger; Lurz, Philipp
Abstract : Background: Renal sympathetic denervation (RDN) as treatment for hypertension shows highly variable results. Although some patients do not show any blood pressure (BP) change and in most patients a BP reduction of at least 5 mmHg can be found, some show a reduction at least 20 mmHg. We sought to identify predictors for such a profound BP response. Methods: Profound BP response was defined as drop of at least 20 mmHg in daytime systolic ambulatory BP measurement (ABPM) 3 months after catheter-based RDN. Three different denervation devices were used for RDN, and pulse wave velocity was determined invasively in a subgroup of patients. Results: One hundred and ninety consecutive patients were included in this analysis. Profound BP response was found in 33 patients. Patients with profound BP response were younger ( P  = 0.04 ), presented with higher baseline ABPM values ( P  < 0.001), were treated with ultrasound-based RDN and received more often a combined treatment with two different diuretics ( P  = 0.005 for both). After 3 months, a treatment target of daytime BP less than 135 mmHg could be achieved more frequently in patients with profound BP response (61 vs. 17%, P  < 0.001). Age, use of ultrasound RDN, combined diuretic therapy and baseline BP independently predicted pronounced BP reduction. A second multivariate logistic regression model including pulse wave velocity if available identified baseline BP, pulse wave velocity and use of ultrasound denervation as independent predictors for profound BP response. Conclusion: Younger vascular age, higher baseline BP, treatment with ultrasound RDN and combined diuretic therapy were found as predictors for a pronounced BP reduction following RDN, improving BP control at follow-up.